Identifikasi Jenis Tangkapan Kmn. Siliwangi Menggunakan Alat Tangkap Purse Seine Di Pelabuhan Perikanan Pantai Mayangan - Wanri Sitanggang; Rifaldo Belmo Da Costa; Herning Pramudya; Daniel Candido Da Costa Soares; Maria Dyah Ayu Pitaloka (Universitas Mataram, 2024)
The Fisheries Potential in Indonesia is vast and spread across the entire waters of Indonesia, which are divided into 11 Fisheries Management Areas (FMA). This regional division aids in fishing activities, resource protection, and fisheries innovation for sustainable utilization. The Mayangan Coastal Fishing Port (CFP) in Probolinggo serves as a facilitator and provider of capture fisheries services, utilizing purse seine fishing gear. This study aims to identify the species and morphology of fish caught by purse seine at the Mayangan CFP. Based on observations and interviews, five dominant fish species were found: Indian mackerel 22% (338,8 kg), Short-bodied mackerel 12% (184,8 kg), Yellowstripe scad 18% (277,2 kg), Round scad 24% (369,6 kg), and Anchovy 24% (369,6 kg). Morphological identification showed variations in size and body shape, influenced by genetic and environmental factors. These results provide important information for effective and sustainable fisheries resource protection and management policies.